Osteogenic/Angiogenic Dual Growth Factor Delivery Microcapsules for Regeneration of Vascularized Bone Tissue. Issue 13 (2nd July 2015) - Subbiah, Ramesh; Hwang, Mintai Peter; Van, Se Young; Do, Sun Hee; Park, Hansoo; Lee, Kangwon; Kim, Sang Heon; Yun, Kyusik; Park, Kwideok
Abstract : Growth factors (GFs) are major biochemical cues for tissue regeneration. Herein, a novel dual GF delivery system is designed composed of poly(lactic‐ co ‐glycolic acid) (PLGA) nanoparticles (NPs) and alginate microcapsules (MCs) via an electrodropping method. While bone morphogenetic protein (BMP)‐2 is encapsulated in the PLGA NPs, vascular endothelial growth factor (VEGF) is included in the alginate MCs, where BMP‐2‐loaded PLGA NPs are entrapped together in the fabrication process. The initial loading efficiencies of BMP‐2 and VEGF are 78% ± 3.6% and 43% ± 1.7%, respectively. When our dual GF‐loaded MCs are assessed for in vitro osteogenesis of umbilical cord blood‐derived mesenchymal stem cells (UCB‐MSCs) on 2D and 3D environment, MCs contribute to much better UCB‐MSCs osteogenesis as confirmed by von Kossa staining, immunofluorescence (osteocalcin, collagen 1), calcium content measurement, and osteogenic markers expression. In addition, when dual GF‐encapsulated MCs are combined with collagen and then applied to 8 mm diameter rat calvarial defect model, the positive effects on vascularized bone regeneration are much more pronounced; micro computed tomography (CT) and histology analyses exhibit 82.3% bone healing coupled with 12.6% vessel occupied area. Put together, current study indicates a synergistic effect of BMP‐2/VEGF and highlights the great potential of dual GF delivery modality (PLGA NPs‐in‐MC) for regeneration of vascularized bone. Abstract : A novel dual growth factor delivery system composed of bone morphogenetic protein (BMP‐2)‐loaded poly(lactic‐ co ‐glycolic acid) (PLGA) NPs and vascular endothelial growth factor (VEGF)‐encapsulated alginate microcapsule (MC) proves a synergistic effect of osteogenic differentiation of umbilical cord blood‐derived mesenchymal stem cells (UCB‐MSC) on 2D and 3D environment in vitro and vascularized bone formation using a rat calvarial bone defect model in vivo.